Regenerative Tourism Experiences in Brazil: An Exploratory Research: uma pesquisa exploratória - Rocha Pereira, Deborah; Francisco de Aragão de Araújo, Tarcísio; Fontes, Claudio Luiz Ariani; Spinola, Carolina de Andrade (RITUR - Revista Iberoamericana de Turismo, 2024)
Increased concern about environmental issues affecting the planet, driven by climate change and the advent of health pandemics, has strengthened the culture of regeneration in various areas of knowledge. It is presented as an evolution of the concept of sustainability. In tourism, this proposition is about two decades old and is still in its infancy in Brazil. In addition to this conceptual discussion, this article aimed to map, through an exploratory search on the internet, the existence of self-declared regenerative tourism experiences and analyze them from the perspective of and analyze them from the perspective of their foundations. The analysis revealed that the emerging culture of regeneration in tourism is influenced by global environmental concerns. By mapping the self-declared experiences of regenerative tourism in Brazil, this study offers pioneering vision practices and foundations. This research reveals not only the incipient nature of regenerative tourism in the country but also its transformative potential. Finally, it was possible to see that public policies and specific guidelines are needed to guide these initiatives. Collaboration between stakeholders and effective implementation of these measures are essential. By integrating these findings into future strategies, Brazil can lead the way globally, promoting conscious and transformative actions for a more resilient and regenerative world.